2020
DOI: 10.1002/ana.25917
|View full text |Cite
|
Sign up to set email alerts
|

Prior Anticoagulation in Patients with Ischemic Stroke and Atrial Fibrillation

Abstract: Objective The aim was to evaluate, in patients with atrial fibrillation (AF) and acute ischemic stroke, the association of prior anticoagulation with vitamin K antagonists (VKAs) or direct oral anticoagulants (DOACs) with stroke severity, utilization of intravenous thrombolysis (IVT), safety of IVT, and 3‐month outcomes. Methods This was a cohort study of consecutive patients (2014–2019) on anticoagulation versus those without (controls) with regard to stroke severity, rates of IVT/mechanical thrombectomy, sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 39 publications
6
86
3
1
Order By: Relevance
“…Indeed, prior NOAC intake represented a major obstacle in administering IVT. These findings are in line with data from conventional in-person settings [ 3 , 5 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, prior NOAC intake represented a major obstacle in administering IVT. These findings are in line with data from conventional in-person settings [ 3 , 5 ].…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, while the relative risk of hemorrhagic strokes has been halved by using NOACs as compared to warfarin, a vitamin K antagonist (VKA), the rate of ischemic stroke has remained largely unchanged [ 1 ]. Consequently, acute ischemic stroke (AIS) develops frequently despite oral anticoagulation [ 2 , 3 ]. Current evidence about the optimal treatment strategies in patients with AIS under therapy with NOACs is still limited [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“… 31 32 However, 18 of the 20 certified stroke units in Switzerland have access to specific tests for patients who had a stroke with comparable safety results and treatment metrics. 33 …”
Section: Drug Monitoring In Doacsmentioning
confidence: 99%
“…The overall reported rate of sICH in this study was 2% (2 patients) and none of the patients selected using DOAC plasma levels had sICH. Data from the Swiss Stroke Registry of 69 patients on DOACs receiving IVT found no increased risk of sICH compared with patients without anticoagulation and those on VKAs with INR ≤1.7 33 (18 of 23 centres used DOAC plasma levels for patient selection).…”
Section: Non-selective Approach To Ivtmentioning
confidence: 99%
“…[3][4][5] Furthermore, it has been reported that the proportion of patients with large vessel occlusion (LVO) at the onset of cerebral infarction is lower in patients receiving DOACs. 6 Moreover, low DOAC plasma levels are reportedly associated with LVO and higher stroke severity on admission to hospital. 7 However, the measurement of plasma DOAC levels is difficult by routine testing in clinical practice.…”
Section: Introductionmentioning
confidence: 99%